THE EFFECT OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) MODEL ON STUDENT LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION FOR GRADE V AT SD INPRES 3 TALISE - Sulastri Miuk; Yusdin Bin. M Gagaramusu; Dyah Rahmawati; Nashrullah; Ammar Abdullah Joni Guci (SOSIOEDUKASI, 2026)
Conventional teaching methods in Islamic Religious Education (PAI) often limit student engagement and conceptual understanding, leading to suboptimal academic performance. This research investigates the impact of the Contextual Teaching and Learning (CTL) model on the learning outcomes of fifth-grade students in the PAI subject at SD Inpres 3 Talise. A quantitative approach utilizing a quasi-experimental Non-Equivalent Control Group Design was employed. The sample consisted of 46 students selected through purposive sampling, divided equally into a control class (VA) and an experimental class (VB). Data collection relied on validated and reliable multiple-choice tests administered as pretests and posttests. Initial baseline assessments indicated equivalent prior knowledge between both groups, with an identical average pretest score of 52.61. Following the intervention, the experimental class, which received instruction via the CTL model, achieved an average posttest score of 81.77. In contrast, the control class, taught using conventional methods, recorded a lower average posttest score of 73.28. Because the data distribution was not normal based on the Shapiro-Wilk test, hypothesis testing was conducted using the non-parametric Mann-Whitney U test. The statistical analysis yielded a significance value of 0.000 (p < 0.05), leading to the rejection of the null hypothesis. The application of the CTL model significantly improves student learning outcomes in PAI by directly connecting theoretical religious concepts to students' real-life experiences, thereby fostering active participation and deeper comprehension.